Efektivitas Penggunaan Media Audiovisual Dalam Pembelajaran Bahasa Inggris Untuk Mahasiswa DIV Manajemen Perhotelan - I Made Krisna Adi Chandra; Made Detri Suryantini (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the effectiveness of using audiovisual media in improving the English language skills of DIV Hotel Management students. The research method used is quantitative with a quasi-experimental design. The research sample consists of two classes of students, namely an experimental class that uses audiovisual media and a control class that uses conventional methods. The research instrument used was an English language proficiency test (pre-test and post-test) covering aspects of listening, speaking, reading, and writing. Data were analyzed using a t-test to determine significant differences between the two groups. The results showed that there was a significant difference in the English language skills of students in the experimental class and the control class after being treated. Students who learned with audiovisual media showed a higher increase in English language skills compared to students who learned with conventional methods. Audiovisual media proved effective in increasing learning motivation, understanding of material, and English language practice skills of students. This research recommends that the use of audiovisual media be integrated into English language learning in the Hotel Management study program to improve the quality of graduates who are ready to compete in the global industry. Further research can develop more innovative and relevant audiovisual media to the needs of the hospitality industry.